Effect of molybdenum on productivity of clusterbean [Cyamopsis tetragonoloba (L.) Taub] varieties - Yadav, Arti; Yadav, L.R.; Yadav, S.S.; Verma, H.P.; Yadav, Neelam (Annals of Agricultural Research, 2018)
A field experiment was conducted at Agronomy farm, S.K.N. College of Agriculture, Jobner(Rajasthan) during kharif, 2015 on loamy sand soil. There were twenty treatment combinationsconsisting of five clusterbean varieties (RGC-936, RGC-1017, RGC-1033, RGC-1002 and RGC-197)and four levels of molybdenum (control, 0.5, 1.0 and 1.5 kg Mo/ha) tested in randomized blockdesign with three replications. Results revealed that variety RGC-1033 proved significantly superiorto RGC- 936, RGC-1017, RGC-1002 and RGC-197 in respect of dry matter accumulation, growthindices like CGR, RGR and LAI, pods/plant, seeds/pod and test weight. Similarly, the seed yield(1862 kg/ha), stover yield (3821 kg/ha) and biological yields (5683 kg/ha) were also significantlyhigher with variety RGC-1033. Result showed that molybdenum application at 1.0 kg/ha significantlyincreased yield attributes of clusterbean (number of pods/plant, number of seeds/pod, test weight)and seed, stover and biological yields. The per cent increase in seed yield with 1.0 kg Mo/ha was22.1 and 8.0, respectively, over control and 0.5 kg Mo/ha. However, application of 1.5 kg Mo/haremained at par with 1.0 kg Mo/ha. Soil application of molybdenum at 1.0 kg/ha gave higher netreturns (Rs. 44813/ha) with higher B:C ratio (2.85) over control and 0.5 kg Mo/ha which was at parwith 1.5 kg Mo/ha (Rs. 42288/ha).